2010
DOI: 10.1186/1476-7120-8-38
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of beta-blocker therapy in symptomatic athletes with exercise-induced intra-ventricular gradients

Abstract: BackgroundUpright exercise stress echocardiography (SE) induces significant intraventricular gradient (IVG) and systolic anterior motion (SAM) in a large proportion of symptomatic athletes, who may therefore benefit from a negative inotropic therapy.The purpose of the present study was to assess the effect of chronic oral β blocker therapy on the occurrence of exercise-induced IVG and mitral valve SAM, in symptomatic athletes.MethodsWe enrolled 35 symptomatic athletes (age = 23 ± 11 years) with IVG (>30 mmHg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
2
16
0
Order By: Relevance
“…Several studies have reported the importance of upright positioning during exercise in the detection of provocable (latent) or labile left ventricular (LV) outflow tract gradients in hypertrophic cardiomyopathy [3][4][5][6][7][8][9][10][11][12]. Also, passive orthostatic tests (without exercise) are helpful in diagnostic evaluation in other diseases predisposing to LV outflow tract gradients [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the importance of upright positioning during exercise in the detection of provocable (latent) or labile left ventricular (LV) outflow tract gradients in hypertrophic cardiomyopathy [3][4][5][6][7][8][9][10][11][12]. Also, passive orthostatic tests (without exercise) are helpful in diagnostic evaluation in other diseases predisposing to LV outflow tract gradients [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 This condition is usually associated to global or segmental left ventricular hypertrophy or an abnormal implantation of the papillary muscles, but the pathophysiological mechanisms are not well established. Three potential mechanisms are purposed for the development of IVG:…”
Section: Discussionmentioning
confidence: 99%
“…The development of significant exercise-induced IVG (>30mmHg at rest or >50mmHg with exercise) is uncommon, but can lead to several and unspecific symptoms such as dizziness, thoracic pain, or even ventricular repolarization changes and arrhythmias during exercise test. 1 , 2 This condition is usually associated to global or segmental left ventricular hypertrophy or an abnormal implantation of the papillary muscles, but the pathophysiological mechanisms are not well established. Three potential mechanisms are purposed for the development of IVG:…”
Section: Discussionmentioning
confidence: 99%
“…We conducted an open-label, prospective, non-randomized study to provide proof of concept that exercise stress echocardiogram can be a guide to tailored treatment in athletes with positive screening [61] and that develop IVG and mitral valve SAM on exertion. We evaluated 52 athletes that developed IVG and 35 (32 had exercise-related symptoms or positive exercise electrocardiography) repeated the exercise stress echocardiogram under treatment with ß blockers Thirty athletes (85%) showed improvement with a significant reduction of IVG and of the prevalence of SAM were shown (Figure 10).…”
Section: Introductionmentioning
confidence: 99%